PENDAYAGUNAAN MODAL SOSIAL PERSPEKTIF EKONOMI ISLAM PADA (STUDI KASUS KOPERASI SYARIAH DI PONDOK PESANTREN UMMUL QUROO SURABAYA) - Muhammad Dinullah; Tika Widiastuti (Universitas Airlangga, 2019)
Islamic economic empowerment is an activity of giving power, ability, or power to the helpless party with effort to help society to improve its ability in creating new entrepreneur in accordance with the laws of the Qur’an and Hadith. In the application of social capital-based that is trust, norm, and network is part of social life that can encourage the achievement of common goals. By means of Sharia cooperative and its network is useful to improve prosperity for society and jama'ah in the scope of hut. So it can empower santri and jama'ah to improve their economy. This research uses descriptive qualitative approach. The research strategy used is case study on Islamic Economic Empowerment based on social capital case study of sharia cooperative in Surabaya. Data collection used is by interview, observation and documentation. The validation technique uses source triangulation and engineering triangulation. Data analysis using the theory put forward by Miles and Huberman. The result of the research based on data analysis shows that the role of Kopontren Ummul Quroo is able to empower and give enough improvement of Islamic welfare where each informant has fulfilled at least the dharuriyat level requirement consisting of clothing needs, food requirement, health requirement, education requirement and requirement vehicle.Keywords: Empowerment, Social Capital, and Sharia Cooperatives